Factors Affecting Implementation Early Initiation of Breastfeeding - Sri Wahyuni Hutabarat; Feedia Mona Saragih; Thaharatun Zuhra; Syarifah Aini Lidia; Sri Rahayu; Sri Herni Harmoni (Fakultas Kebidanan Institut Kesehatan Medistra Lubuk Pakam, 2025)
Early breastfeeding initiation (EBI) is the stage of breastfeeding that begins immediately after birth, where the baby is placed in skin contact with the mother. This process lasts for at least one hour. This process brings various benefits, both for the baby and the mother. However, the implementation of Early Breastfeeding Initiation (EBI) is often caused by various factors, both from within the mother and from the surrounding environment. The following study aims to identify factors that can influence the implementation of IMD at Butar Community Health Centre. The type of research conducted is descriptive analytics through a cross-sectional design. The population in the following study includes all mothers who received delivery services at Butar Community Health Centre during the period July to November, with a total of 128 people. A total of 103 respondents were selected as samples using the Slovin formula technique. Data analysis was carried out univariately and bivariately by applying the chi-square test. The study results showed a p-value of 0.000<0.05, which proves that there is no significant correlation between husband support and the implementation of Early Breastfeeding Initiation (EBI). In addition, a p-value of 0.900 > 0.05 also indicates that there is no significant correlation between community trust and the implementation of EBF. It is hoped that this research will motivate all health workers and health service providers to better understand the EBF protocol in accordance with WHO and Ministry of Health standards. Furthermore, it is hoped that the officers will be able to encourage mothers to immediately carry out EBF after receiving delivery assistance.